2023
DOI: 10.1186/s13068-023-02346-8
|View full text |Cite
|
Sign up to set email alerts
|

The metabolome and bacterial composition of high-moisture Italian ryegrass silage inoculated with lactic acid bacteria during ensiling

Abstract: Background With its high nutritional value and productivity, Italian ryegrass as a biomass feedstock constantly supplies rumen degradable nitrogen and digestible fiber to ruminants. However, biofuel production is easily reduced during ensiling due to the high-moisture content of Italian ryegrass, leading to economic losses. Lactic acid bacteria inoculants could improve lignocellulosic degradation and fermentation quality and decrease dry matter loss during the bioprocessing of silage. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The variation in DM loss resulting from different DM contents during ensiling can be attributed to the presence of a highly active microbial population and a faster rate of fermentation in low-DM silage, as these factors may promote oxidation of organic matter (Wilkinson and Davies 2013 ; Kim et al 2016 ). Ensiling low-DM forages may delay pH reduction, possibly causing a less inhibitory effect on the growth and activity of undesirable microorganisms, which thus may increase nutrient loss during the early stages of ensiling fermentation (Ellis et al 2016 ; Xia et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation in DM loss resulting from different DM contents during ensiling can be attributed to the presence of a highly active microbial population and a faster rate of fermentation in low-DM silage, as these factors may promote oxidation of organic matter (Wilkinson and Davies 2013 ; Kim et al 2016 ). Ensiling low-DM forages may delay pH reduction, possibly causing a less inhibitory effect on the growth and activity of undesirable microorganisms, which thus may increase nutrient loss during the early stages of ensiling fermentation (Ellis et al 2016 ; Xia et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Xia et al ( 2023 ) investigated the impact of L. rhamnosus inoculation on the metabolome profile of low-DM (17.7%) Italian ryegrass silage. The authors reported that this homofermentative strain resulted in an upregulation of flavonoid compounds in the flavone and flavonol biosynthesis pathway, which thereby increased apigenin concentration after 60 days of ensiling fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Libraries for sequencing were prepared by Macrogen Inc. using the primers 799F: AACMGGATTAGATACCCKG and 1193R: ACGTCATCCCCACCTTCC. These primers have been frequently used in metabarcoding studies and are highly specific for amplifying bacterial sequences in grasses (Liu, Tang, et al, 2022; Xia et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Glucose fermentation carried out by lactic acid bacteria leads to the production of organic acids like lactic acid and acetic acid [61]. These organic acids serve as the primary products of lactic acid bacteria fermentation, contributing to the regulation of the acid-base balance and inhibition of the growth of other detrimental microorganisms [62]. Simultaneously, organic acids also serve as a significant means of nitrite degradation.…”
Section: Metabolite Analysis Of L Plantarum A50mentioning
confidence: 99%